MANAGEMENT OF HYPERTENSIVE PDA - Khattak, Khushal Khan; Ullah, Maad; Sheikh, Abdul Malik; Kanwal, Asma; Shah, Sajid Ali; Nisa, Noor -Un- (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine different treatment options in patients of Patent Ductus Arteriosus with pulmonary hypertension beyond neonatal period. Study Design: Descriptive cross sectional study. Place and Duration of Study: This study was carried out in Pediatric Cardiology department of Rawalpindi Institute of Cardiology, from Jan 2017 to Jan 2019. Methodology: Patients having PDA with pulmonary hypertension were included in the study. Treatment options were divided into percutaneous catheter device closure, surgical ligation of patent ductus arteriosus and palliative treatment. Any adverse event during the procedure was documented. Stratification was done in regard to gender and age group. Post stratification chi square test was applied and p-value less than or equal to 0.05 was considered as significant. Results: Total number of patients included in the study were 37. Mean age (years) of patients (Mean ± SD) was 19.21 ± 8.76. Mean ± SD pulmonary artery pressure was 56.43 ± 11.55 mmHg. Percutaneous catheter device closure was successful in 24 (64.9%) patients, in 7 (18.9%) patients primary surgical PDA ligation was done, 3 (8.1%) patients were advised palliative treatment and in 3 (8.1%) patients adverse events occurred during percutaneous device closure and were thus referred for surgical ligation. Patent ductus Arteriosus Occlutech device was used in 18 (48.6%) patients, Occlutech VSD device was used in 7 (18.5%) patients and in 1 (2.7%) patient AGA duct occluder was used. Conclusion: In patients with patent ductus arteriosus and pulmonary artery hypertension, percutaneous catheter device closure is a safe and effective procedure.